Chemical, Physical, and Biological Corneal Decellularization Methods: A Review of Literature - Alexandra Procházková; Martina Poláchová; Jakub Dítě; Magdaléna Netuková; Pavel Studený (Journal of Ophthalmology)
The cornea is one of the most commonly transplanted tissues worldwide. It is used to restore vision when severe visual impairment or blindness occurs in patients with corneal diseases or after trauma. Due to the global shortage of healthy donor corneas, decellularized corneal tissue has significant potential as an alternative to corneal transplantation. It preserves the native and biological ultrastructure of the cornea and, therefore, represents the most promising scaffold. This article discusses different methods of corneal decellularization based on the current literature. We searched PubMed.gov for articles from January 2009 to December 2023 using the following keywords: corneal decellularization, decellularization methods, and corneal transplantation. Although several methods of decellularization of corneal tissue have been reported, a universal standardised protocol of corneal decellularization has not yet been introduced. In general, a combination of decellularization methods has been used for efficient decellularization while preserving the optimal properties of the corneal tissue.